2023
DOI: 10.3390/fermentation9090852
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Weevil (Rhynchophorus palmarum), Teosinte (Dioon mejiae) and Caesar’s Mushroom (Amanita caesarea) on the Properties of Lactobacillus acidophilus LA-K

Ricardo S. Aleman,
Dany Avila,
Allan Avila
et al.

Abstract: Weevil (Rhynchophorus palmarum) powder, teosinte (Dioon mejiae) and Caesar’s mushroom (Amanita caesarea) flour have bioactive compounds with significant nutritional applications. This paper aimed to examine the influence of weevil, teosinte, and mushroom powders on the protease activity, acid tolerance, bile tolerance, lysozyme tolerance, and gastric juice resistance ability of Lactobacillus acidophilus LA-K. Acid tolerance was determined by adjusting the pH of MRS broth to 2.0 for L. acidophilus incubated und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Furthermore, for other plants, such as carao (Cassia grandis), Paz et al (2022) [20] reported the bile tolerance of L. bulgaricus over 8 h of incubation in MRS broth, with it having 0.03% oxgall and improvement with growth. In addition, showed that Caesar mushroom and weevil powders inhibit the growth of L. acidophilus under oxgall salt (0.03%) in MRS broth [21]. The bile in the gallbladder originates in the liver.…”
Section: Bile Tolerancementioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, for other plants, such as carao (Cassia grandis), Paz et al (2022) [20] reported the bile tolerance of L. bulgaricus over 8 h of incubation in MRS broth, with it having 0.03% oxgall and improvement with growth. In addition, showed that Caesar mushroom and weevil powders inhibit the growth of L. acidophilus under oxgall salt (0.03%) in MRS broth [21]. The bile in the gallbladder originates in the liver.…”
Section: Bile Tolerancementioning
confidence: 99%
“…Aleman et al ( 2023) [19] examined the acid tolerance of L. acidophilus and concluded that nipple fruit improved the growth in MRS broth. In addition, Aleman et al (2023) [21] showed that Caesar mushroom and weevil powders inhibit the growth of L. acidophilus under acidic conditions. The buffering capacity of potential compounds in the nipple fruit could prevent bacteria decay under acidified conditions.…”
Section: Acid Tolerance and Resistance To Gastrointestinal Juicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Fruits and other plant-derived products have the potential to serve as effective substrates for probiotics, given their content of vitamins, minerals, fiber, carbohydrates, and antioxidant elements [4]. Recently, the probiotic properties of lactic acid bacteria were examined concerning new food sources such as weevil (Rhynchophorus palmarum), nipple fruit (Solanum mammosum), teosinte (Dioon mejiae), and Caesar mushroom (Amanita caesarea) [5][6][7][8][9]. Carao has been used in yogurt and it shows great antioxidant and hypoglycemic potential [10].…”
Section: Introductionmentioning
confidence: 99%